2017
DOI: 10.2147/jn.s132589
|View full text |Cite
|
Sign up to set email alerts
|

2016 yearbook of neurorestoratology

Abstract: Neurorestoratology, a new interdisciplinary field, has gradually become a popular clinical discipline. Physicians and scientists in the neurorestoration field have discovered new pathogeneses of nervous system diseases and damage, explored new neurorestorative mechanisms, and obtained improving neurorestorative effects in clinical trials (or therapies). This paper summarizes the major progress achieved over the past year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Moreover, if patients are treated combine with other neurorestoring methods, such as cell therapy [9], neuromodulation, suitable rehabilitation etc. [19,20], they may have less recurrence and achieve better therapeutic effect. This could also be the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if patients are treated combine with other neurorestoring methods, such as cell therapy [9], neuromodulation, suitable rehabilitation etc. [19,20], they may have less recurrence and achieve better therapeutic effect. This could also be the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Currently clinical neurorestorative therapies are able to help patients with central nervous system (CNS) diseases or damage for improving their neurological function and quality of life following complete chronic spinal cord injury (SCI), stroke, amyotrophic lateral sclerosis (ALS) and many other diseases [1,2]. Although, these advancements were made in due course of time [3,4]; incorrect viewpoints about clinical neurorestorative treatment strategies are still noticed in this area, with special reference to SCI. This appears to be a common misunderstanding that "there are no any methods for restoring damaged neurological structure or functions so far, or even partial restoration" [5].…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of Neurorestoratology as a new clinical discipline depends a great deal on dissemination of its progress. For this reason, we published the first "Yearbook of Neurorestoratology" in 2016 [1]. Assembly of the 2017 "Yearbook of Neurorestoratology" is a work in progress, and is intended to collect and summarize: (1) new finding relating to disease pathogenesis or damage to the nervous system; (2) new neurorestorative pathogenesis of central nervous system diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we published the first "Yearbook of Neurorestoratology" in 2016 [1]. Assembly of the 2017 "Yearbook of Neurorestoratology" is a work in progress, and is intended to collect and summarize: (1) new finding relating to disease pathogenesis or damage to the nervous system; (2) new neurorestorative pathogenesis of central nervous system diseases. Huang et al found that lower expression of SPI1 (encoding PU.1) in microglial cells can reduce Alzheimer disease (AD) risk by regulating myeloid gene expression and phagocytic activity [2].…”
Section: Introductionmentioning
confidence: 99%